Multiplex genotyping of PCR products with MassTag-labeled primers. - Haff, L A (1997)
A simple mass spectrometric based assay, the PinPoint assay, has previously been described for typing single nucleotide polymorphisms. The identity of a polymorphism is determined by mass differences of single base extended genotyping primers as determined by MALDI-TOF mass spectrometry. A simple method for multiplexing the assay is described, employing multiple primers with 5'oligo(dT) sequences (MassTags) which serve to mass discriminate the peaks of multiple extended and non-extended primers. The assay is extremely rapid and requires no labeling reagents.